Effect of strength and endurance training sequence on endurance performance - Vikestad, V.; Dalen, T. (Sports, 2024)
This review investigates the effect of two different concurrent training sequences on endurance performance. The sequences investigated are Endurance-Resistance (ER) and Resistance-Endurance (RE). A literature search is conducted of the SPORTDiscus and Medline databases. The included studies are randomized control trials, which compare the effect of ER and RE on at least one endurance performance variable. A PEDro scale is used to assess the methodological quality of the articles in this review. Of a total of 152 articles identified during the initial screening, 15 studies meet the inclusion criteria. These studies include 426 participants (298 males and 128 females), with 212 of the participants training with ER and 214 with RE. The results are presented as the percentage change of the mean from pre- to post-test. All the studies show an improvement in endurance from pre to post for both interventions, except for the RE group in one study. This review finds small and non-conclusive sequence effects between ER and RE, suggesting that the sequence of concurrent training is not of great importance in relation to endurance performance.